PROCUREMENT AUCTIONS WITH RENEGOTIATION AND WEALTH CONSTRAINTS. (17th February 2016) - Chang, Wei‐Shiun; Salmon, Timothy C.; Saral, Krista J.
Abstract : Renegotiation is a common practice in procurement auctions which allows for postauction price adjustments and is nominally intended to deal with the problem that sellers might underestimate the eventual costs of a project during the auction. Using a combination of theory and experiments, we examine the effectiveness of renegotiation at solving this problem. Our findings demonstrate that renegotiation is rarely successful at solving the problem of sellers misestimating costs. The primary effect of allowing renegotiation is that it advantages sellers who possess a credible commitment of default should they have underbid the project. Renegotiation allows these weaker types of sellers to win more often and it also allows them to leverage their commitment of default into higher prices in renegotiation from a buyer. ( JEL C91, D44, D82)